Responses of protist communities to spatio-temporal changes in water masses in the northeastern East China Sea in 2023 - Hye Jin Seo; Hyun Jun Yang; Yun Hee Kim; Dohyeop Yoo; Hyebin Kim; Jiae Yoo; Sunju Kim; Yoonja Kang; Tae-Hoon Kim; Byoung-Ju Choi; Adrian Marchetti; Se Hyeon Jang (Algae, 2026)
This study explores the dynamics of protist communities in the northeastern East China Sea (ECS) focusing on their responses to changing water masses and oceanographic conditions during spring, summer, and autumn in 2023. Water masses were classified using K-means clustering based on physico-chemical parameters, revealing significant seasonal variation. Protist community spatial, temporal, and vertical distributions were analyzed using 18S rRNA gene amplicon sequencing and morphological identification along the 33° N latitude, a region characterized by the confluence of multiple water masses, including Kuroshio surface (KSW) and sub-surface (KSSW) waters, Yellow Sea water (YSW), Changjiang diluted water (CDW), and ECS Shelf water. Protist diversity, community structure, and cell abundance exhibited pronounced seasonal variations influenced by temperature, salinity, and nutrient availability. In spring, YSW, characterized by phosphate deficiencies and, consequently, increased N : P ratios, exhibited a prevalence of dinoflagellates, whose phagotrophic capabilities likely conferred a competitive advantage in such nutrientfluctuating environments. During summer, diatoms were prevalent in the ECS Shelf water, underscoring the role this water plays in shaping seasonal community structure. In contrast, CDW exhibited low species diversities, likely due to unstable salinity. In autumn, water column mixing increased overall diversity and cell abundance, particularly in YSW, where Chaetoceros socialis and other diatoms thrived. Potential phosphorus limitation, especially in the western waters, may have further influenced the spatial structuring of communities across seasons. These findings highlight complex interactions between oceanographic factors and protistan communities in the northeastern ECS, contributing to a deeper understanding of their distributions and responses to environmental changes.

Migration of organic and inorganic antimicrobials from antimicrobial-labeled food packaging and probabilistic risk assessment implications - Kyung Youn Lee; Hogeon Lee; Hee Seon Shin; Da Hee Ryu; Hyebin Yeo; Hae Min Ju; Dae Yong Jang; Ye Ji Koo; Seung Ha Lee; Kyung Min Lim; Dal Woong Choi (Food Packaging and Shelf Life, 2025)

Filter-assisted sample preparation for on-site detection using a bi-functional linker-based biosensor demonstrated with Escherichia coli O157:H7 - Hyebin Han; Seung Hwan Ham; Youngsang You; Jihae Lee; Jungwoo Hahn; Young Jin Choi (Food Chemistry, 2025)

Production and application of Paenibacillus polymyxa levan as an antiviral priming agent against cucumber mosaic virus infection in tobacco plants - Hyunjun Ko; Hangil Kim; Ji Won Heo; Sangjun Lee; Yongtae Yu; Hyebin Kim; Hyeon-Seok Oh; Chan-Gi Min; Seokmin Baek; Han Suk Choi; Sung Jin Moon; Woohyun Sim; et al. (Carbohydrate Polymers, 2025)

Proteomics Reveals Plasma Biomarkers for Ischemic Stroke Related to the Coagulation Cascade - Jiyeong Lee; Sora Mun; Arum Park; Doojin Kim; Yoo-Jin Lee; Hyo-Jin Kim; Hyebin Choi; Miji Shin; Soo Joo Lee; Jae Guk Kim; Yeon Tae Chun; Hee-Gyoo Kang (Journal of Molecular Neuroscience, 2020)